Respuesta :
Answer:
A. StartRoot 3 EndRoot.
Step-by-step explanation:
We have to simplify the following expression
[tex]2\sqrt{27} + \sqrt{12} - 3\sqrt{3} - 2\sqrt{12}[/tex]
Now, we know that 27 = 3 × 3 × 3, hence [tex]\sqrt{27} = 3 \sqrt{3}[/tex].
And 12 = 2 × 2 × 3, hence [tex]\sqrt{12} = 2 \sqrt{3}[/tex]
So, the given expression becomes
[tex]2\sqrt{27} + \sqrt{12} - 3\sqrt{3} - 2\sqrt{12}[/tex]
= 2 × 3√3 + 2√3 - 3√3 - 2 × 2√3
= 6√3 + 2√3 - 3√3 - 4√3
= √3
Therefore, the solution is A. StartRoot 3 EndRoot. (Answer)